iSpeak-Smart: A Differentiated Mobile Learning Medium for Public Speaking Courses to Stimulate Students’ Interpersonal Intelligence and Self-Regulated Learning - Siti Nurun Chumairoh; Madziatul Churiyah; Ardian Novianti (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2026)
The rapid transformation of vocational education demands innovative digital environments that cultivate professional communication and independent learning skills. Static, unstructured learning resources often lead to low interpersonal intelligence and self-regulated learning (SRL) among students. This study developed and tested the effectiveness of iSpeak-Smart, a knowledge-based mobile learning system designed to stimulate interpersonal intelligence and improve students’ SRL in an adaptive and personalized manner within the Public Speaking subject at SMK Negeri 1 Malang. This study employed the Research and Development (R&D) method using the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. Quantitative data from validation results, practicality questionnaires, and test scores were analyzed using descriptive statistics and the N-Gain Score, while qualitative data were collected through interviews with teachers and students and validator suggestion sheets. iSpeak-Smart met the “very feasible” criteria for content, language, and graphics, with an average validation score above 88%. The media significantly increased students’ interpersonal intelligence in empathy, effective communication, and social interaction, and significantly improved SRL, particularly in planning, monitoring, and evaluating independent learning. It also increased learning motivation through differentiated learning, gradual scaffolding, and self-reflection, fostering a meaningful, mindful, and enjoyable learning experience. iSpeak-Smart is proven effective as an adaptive learning ecosystem integrating public speaking skills, interpersonal intelligence, and SRL development, supporting digital learning practices in vocational high schools (SMK) amid the challenges of dynamic and heterogeneous communication learning in educational digitalization.